The Depiction of Post Traumatic Stress Disorder from The Main Character in In The Shadow of No Towers Graphic Novel (PANOPTICON: Journal of English Studies, 2024)
The purpose of this research is to analyze psychoanalytic issues, specifically post-traumatic stress disorder (PTSD), as depicted in the graphic novel In the Shadow of No Towers (2002) by Art Spiegelman. The study utilizes a descriptive qualitative method to gather and interpret data from the text, focusing on how PTSD is portrayed. Data collection involved a detailed examination of the graphic novel, capturing how Spiegelman illustrates the trauma and psychological impact of the September 11, 2001, World Trade Center attacks, which affected him personally. The analysis is guided by Cathy Charut's (1996) theory of post-trauma, which provides a framework for understanding how traumatic events are represented and processed. The results reveal that In the Shadow of No Towers vividly portrays PTSD through its narrative and visual elements, reflecting Spiegelman's own experiences and emotional responses to the attacks. The graphic novel's depiction of trauma is analyzed to show how it affects the author's psyche and how it manifests in his work. This study contributes to the understanding of trauma representation in graphic literature.